A Review on Hypertensive Drug Prescription - Joshi, Prashant; Singh, Sanjay; Sanwal, Ritu (Asian Journal of Pharmaceutical Research and Development, 2022)
Hypertension is considered to be the vital reason of mobidity and mortality in the society. It is an important risk aspect for cerebro-vascular, cardiovascular, and renal problems. A number of national and international guidelines for the management of hypertension have been published. The increasing occurrence of hypertension and the frequently escalating expenditure of its treatment control the prescribing patterns amongst physicians and compliance to the treatment by the patients. from the time when several years ago, diuretics were calculated as the first-line drugs for management of hypertension therapy; however, the recent guidelines by the Joint National Commission (JNC8 guidelines) advise both calcium channel blockers in addition to angiotensin converting enzyme inhibitors as first-line drugs, in adding up to diuretics. This assessment aims on the antihypertensive medication utilization, adherence to treatment by patients, and physicians’ adherence to guidelines in prescribing medications in various settings. The antihypertensive medication prescribing pattern studies assist to observe, estimate and essential changes to the prescribing practice to get rational and cost-effective treatment. In addition, there should always be an updating of recommended guidelines and inventive drug formulations, and prescription monitoring evaluations help in rational use of antihypertensive drugs, which can be tailored to go with the patients' requirements, counting those in the emergent countries.